Time Orientation and its Relationship with Goal Orientation - Atoum, Adnan; Al-Bashtawi, Khaled; Al-Momani, Abdel Lateef (Advances in Social Sciences Research Journal, 2020)
The objectives of the study are to investigate time orientation and goal orientation levels in light of some variables, and to identify the relationship between the two variables. The sample of the study consists of 698 male and female students studding at Yarmouk University. Zimbardo and Boyd (1999) Time Orientation Scale and Abu Ghazal et al., (2013) Goal Orientation Scale are used after assessing the validity and reliability for both scales. The results of the study showed that the past positive domain in time orientation ranked first, followed by future past negative, present hedonism, present fatalistic, respectively. The results also showed that the domain of mastery-approach in goal orientations ranked first, followed by performance-avoidance, and finally performance-approach. The results of the study indicated a statistically significant positive correlations between future time orientation and mastery- approach goal orientation, and between past negative time orientation and performance- avoidance goal orientation. There are statistically significant positive correlations between time orientation domains and goals orientations domains except a negative correlation between present fatalistic time orientation and mastery-approach goal orientation